2016
DOI: 10.1038/srep26551
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional analysis of two novel connexin 50 mutations associated with autosome dominant congenital cataracts

Abstract: Autosomal dominant congenital cataracts (ADCC) are clinically and genetically heterogeneous diseases. The present study recruited two Chinese families with bilateral nuclear cataract or zonular pulverulent phenotype. Direct sequencing of candidate genes identified two novel missense mutations of Cx50, Cx50P59A (c.175C > G) and Cx50R76H (c.227G > A), both co-segregated well with all affected individuals. Bioinformatics analysis predicted deleterious for both mutations. Functional and cellular behaviors of wild … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…According to the prediction tools (Table ), the mutation is damaging and disease‐causing. A heterozygous mutation (P59A) located within the first extracellular domain of GJA8, which is also in close proximity with N55K, has been reported in a Chinese family to cause a zonular pulverulent . Due to the presence of P59A, the GJA8 protein was unable to assemble at the site of cell‐cell apposition leading to the lack of gap junction formation .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the prediction tools (Table ), the mutation is damaging and disease‐causing. A heterozygous mutation (P59A) located within the first extracellular domain of GJA8, which is also in close proximity with N55K, has been reported in a Chinese family to cause a zonular pulverulent . Due to the presence of P59A, the GJA8 protein was unable to assemble at the site of cell‐cell apposition leading to the lack of gap junction formation .…”
Section: Discussionmentioning
confidence: 99%
“…A heterozygous mutation (P59A) located within the first extracellular domain of GJA8, which is also in close proximity with N55K, has been reported in a Chinese family to cause a zonular pulverulent. 26 Due to the presence of P59A, the GJA8 protein was unable to assemble at the site of cell-cell apposition leading to the lack of gap junction formation. 26 Since N55K and P59A are in the same domain, we postulate that both mutations might have similar effect on the GJA8 functionality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gap junction channels in lens fiber cells are mainly formed by gap junction proteins connexin‐46 and connexin‐50, encoded by GJA3 and GJA8 , respectively (Gong et al, ). Many missense and frameshift mutations of GJA3 and GJA8 have been identified in members of families with inherited cataracts, typically autosomal‐dominant nuclear and zonular pulverulent cataracts (Mackay et al, ; Rees et al, ; Yao et al, ; Zhu et al, ; Yu et al, ). Functional studies of some mutant connexin proteins have revealed that mutations cause altered gap junction properties and altered cell surface expression, thus compromising intercellular communication and resulting in lens opacities (Gao et al, ; Beyer et al, ; Yu et al, ).…”
Section: Genetics Of Congenital Cataracts and Childhood Risk Factorsmentioning
confidence: 99%
“…In addition, some nonsyndromic cataracts could include the presence of lens opacities only or lens opacities with ocular abnormalities and with no systemic affection, i.e., microcornea, aniridia, vitreoretinochoroidopathy, microphthalmia, anophthalmia, iris hypoplasia, or rod-cone dystrophy ( Table 4 ). Graw et al, 2009;Hansen et al, 2009;Wang et al, 2009;Gao et al, 2010;He et al, 2011;Kumar at al., 2011;Sun et al, 2011a;Wang L et al, 2011;Ponnam et al, 2013;Reis et al, 2013;Su et al, 2013;Chen et al, 2014;Ge et al, 2014;Gillespie et al, 2014;Mackay et al, 2014;Prokudin et al, 2014;Sun et al, 2014;Zhu et al, 2014;Chen et al, 2015;Liang et al, 2015;Yang Z et al, 2015;Min et al, 2016;Yu et al, 2016 9q21 Litt et al, 1998;Pras et al, 2000;Mackay et al, 2003;Graw et al, 2006;Santhiya et al, 2006;Vanita et al, 2006;Beby et al, 2007;Hansen et al, 2007;Khan et al, 2007;Devi et al, 2008;Gu et al, 2008;Richter et al, 2008;Hansen et al, 2009;Santana et al, 2009;Zhang ...…”
Section: Nonsyndromic Cataractsmentioning
confidence: 99%